CAUSES OF ETHNIC CLASHES IN KAZAKHSTAN - Lim, Vlad (Nazarbayev University School of Sciences and Humanities, 2021)
In this research, I analyze the causes of violent confrontations that have taken place in Kazakhstan since independence. In particular, I close an important gap in the literature: most works have focused on certain aspects of ethnic problems in the country, such as language, migration, and Kazakhization, while the causes of violent clashes themselves have been understudied. Thus, my research demonstrates the roots of grievances that lead to mobilization of the titular ethnic group along ethnic lines. I studied the conducive role of Kazakhization on the perception of ethnic superiority among Kazakhs, demonstrating how the government promotes Kazakhness among population. Kazakhization has played an important role contributing to the level of grievances among ethnic Kazakhs. Also, I conducted a careful case selection to find the most suitable cases for examination. I created a sample with three pairs of villages with common characteristics, where non Kazakh ethnic groups form the majority. The only difference between the pairs was the outcome. Thus, one sample from each pair experienced violent confrontations, while the other did not. Once I finished selecting cases, I proceeded to the actual examination of the theory. I studied the existence of two essential conditions thatseed the feeling ofdeprivation and can be responsible forthe variation across the pairs: poverty and inequality. Specifically, by looking at the data that measures level of poverty, I show a correlation between violent confrontations and poverty rate. However, taking into account that poverty is a common feature to all villages from my Sample size, I found that it is the perception of inequality that is responsible for the variation. Since the data on violent clashes in Kazakhstan is quite limited and can hardly be complete and reliable, I conducted a field study, where I collected first-source data from surveys and in-depth interviews. The data from my field trip reveals the correspondence between the feeling of relative inequality, reinforced grievances and the outcome. Moreover, it shows that the ethnic distribution of business ownership can be a trigger that determines the outcome. To be more specific, in the villages where major businesses and properties belonged to ethnic Kazakhs, violent clashes did not occur, whilst in the villages, where major businesses and properties belonged to ethnic minorities, violent confrontation did occur. Thus, building on the theory of relative deprivation I reveal how business ownership leads to the feelings of deprivation and subsequent grievances, which results in violent confrontations
Keywords: Type of access: Open Access; ethnic relations; USSR; violent confrontations